2020
DOI: 10.1177/0194599820935395
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Squamous Cell Carcinoma Outcomes: Does Treatment at a High‐Volume Center Confer Survival Benefit?

Abstract: Objective To determine whether treatment of sinonasal squamous cell carcinoma (SCC) at a high-volume facility affects survival. Study Design Retrospective database analysis. Setting National Cancer Database (2004-2014). Subjects and Methods The National Cancer Database was queried for sinonasal SCC from 2004 to 2014. Patient demographics, tumor characteristics and classification, resection margins, treatment regimen, and facility case-specific volume—averaged per year and grouped in tertiles as low (0%-33%), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
(77 reference statements)
2
10
0
1
Order By: Relevance
“…Teitelbaum et al [ 6 ▪ ] (3835 patients) showed that patients affected by sinonasal squamous cell carcinoma (SCC) treated in high-volume centers (>16 patients/10 years) had a significantly better prognosis than those treated in low-volume centers (<12 patients/10 years) regardless of age, sex, T category, and treatment schedule. Of note, the majority (55.5%) of patients included in the study received a surgery-including treatment.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Teitelbaum et al [ 6 ▪ ] (3835 patients) showed that patients affected by sinonasal squamous cell carcinoma (SCC) treated in high-volume centers (>16 patients/10 years) had a significantly better prognosis than those treated in low-volume centers (<12 patients/10 years) regardless of age, sex, T category, and treatment schedule. Of note, the majority (55.5%) of patients included in the study received a surgery-including treatment.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…With the emergence of endoscopic surgery, the treatment of these cancers requires an additional technicality, which due to the rarity of these lesions, can only be acquired in specialized centers. For example, studies performed on the NCDB database have shown that the survival of patients with squamous cell carcinoma of the nasal cavity is increased in the center with a large track record of this type of disease [140] and that centers treating more than two patients per year were associated with a higher rate of clear margins [42]. It has been shown that surgical experience may be associated with increased overall survival and local control in patients treated endoscopically for sinonasal adenocarcinoma [92,141].…”
Section: Surgeon-related Criteriamentioning
confidence: 99%
“…Orbital preservation best represents the compromise made to achieve acceptable oncological results while maximizing functional outcomes (8). Therefore, sinonasal tumors are indeed an example of multidisciplinarity and should be best performed at high volume centers (9), a statement that of course is challenged by the rarity of these tumors and their variable presentations and histologies.…”
Section: Introductionmentioning
confidence: 99%